Choroidal Thickness in Healthy Chinese Subjects - Ding, Xiaoyan; Li, Jiaqing; Zeng, Jing; Ma, Wei; Liu, Ran; Li, Tao; Yu, Shanshan; Tang, Shibo (Investigative ophthalmology & visual science, 2011)
To study posterior choroidal thickness and its profile based on location in a healthy Chinese population and to determine its correlation with age and refractive error. A total of 210 healthy volunteers (420 eyes) with no ophthalmic disease history were recruited. Choroidal scans were obtained for all eyes using enhanced depth imaging spectral-domain optical coherence tomography. Subfoveal choroidal thickness (SFCT) and choroidal thickness at 1 mm/3 mm temporal, nasal, superior, and inferior to the fovea were measured. The choroid was thickest underneath the fovea (261.93 ± 88.42 μm). At 1 mm and 3 mm to the fovea, the choroid temporally was thicker than nasally. Mean SFCT in subjects younger than 60 years of age were 294.63 ± 75.90 μm, and no correlation between SFCT and age was noted. Mean SFCT in subjects older than 60 years of age was 196.52 ± 74.42 μm, much thinner than that for subjects younger than 60 years of age. A significant negative correlation was found between SFCT and age in subjects older than 60 years of age. Age is critical for evaluation of choroidal thickness. However, SFCT has no correlation with age in subjects younger than 60 years of age. In subjects older than 60 years of age, SFCT was significantly negatively correlated with age, and decreased by 5.40 μm for each year of life.